How Communication experts express communicative competence - Eliana Mara Braga; Maria Júlia Paes da Silva
This study aimed at understanding how Brazilian communication specialists express their communicative competence. A group of nursing professors, who were communication experts, was investigated by means of a guiding question, namely, "How do you express your communicative competence?". The interviewees reported that they expressed their communicative competence by experiencing it in their professional lives and daily routines, listening to other people, perceiving nonverbal communication, validating message comprehension, breaking communication barriers, showing affectivity and developing self-knowledge. The results obtained from this study enabled us to understand communication as something to be learned, felt and experienced, i.e. by perceiving our own emotions and feelings as well as those of other people, both in nursing care and in everyday actions.